An Analysis of Directives Speech Acts in Film Script of Iron Man 2 (2010) - Arini Hidayah (Surakarta English and Literature Journal, 2019)
The objectives of this study are to find directives speech acts and to explain how directives speech acts which performed in the film Iron Man 2. This research belongs to qualitative research. This research uses purposive sampling techniques in order to analyz directives speech acts. This research instruments which used are Laptop, internet, and film Iron Man 2. In analysing data, the researcher conducted the analysis by describing the context of data, identifying each utterance’s directive, and classifying directives category. There are 152 directives speech acts found in the film Iron Man 2. In details, 152 directive speech acts comprises 6 advising, 20 commanding, 26 ordering, 76 questioning and 24 requesting. It means that directives speech acts can unfold the characterization of characters in film.